2020
DOI: 10.1007/s00018-020-03616-6
|View full text |Cite
|
Sign up to set email alerts
|

The ZIP6/ZIP10 heteromer is essential for the zinc-mediated trigger of mitosis

Abstract: Zinc has been known to be essential for cell division for over 40 years but the molecular pathways involved remain elusive. Cellular zinc import across biological membranes necessitates the help of zinc transporters such as the SLC39A family of ZIP transporters. We have discovered a molecular process that explains why zinc is required for cell division, involving two highly regulated zinc transporters, as a heteromer of ZIP6 and ZIP10, providing the means of cellular zinc entry at a specific time of the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 81 publications
3
48
0
Order By: Relevance
“… 33 Driven by STAT3, SLC39A10 was also found to interact with SLC39A6 to initiate cell rounding and import zinc into cells to initiate mitosis. 39 In the current study, flow cytometry results demonstrated that SLC39A10 knockdown promoted the apoptosis of HCC cells. Furthermore, the mRNA and protein expression of two important apoptosis inhibitors, BCL-2 and BIRC5/survivin, were proportionally reduced in HCC SLC39A10-knockdown cells.…”
Section: Discussionsupporting
confidence: 50%
“… 33 Driven by STAT3, SLC39A10 was also found to interact with SLC39A6 to initiate cell rounding and import zinc into cells to initiate mitosis. 39 In the current study, flow cytometry results demonstrated that SLC39A10 knockdown promoted the apoptosis of HCC cells. Furthermore, the mRNA and protein expression of two important apoptosis inhibitors, BCL-2 and BIRC5/survivin, were proportionally reduced in HCC SLC39A10-knockdown cells.…”
Section: Discussionsupporting
confidence: 50%
“…ZIP6 and ZIP10 can form respective homodimers targeted to the plasma membrane where they mediate cellular zinc uptake, which often triggers cells to undergo epithelial-to-mesenchymal transition (EMT) ( 86 , 87 , 128 , 129 ), a process by which epithelial cells lose their cell–cell adhesion and gain migratory properties to become multipotent mesenchymal stem cells during embryonic development and tissue regeneration. Interestingly, ZIP6–ZIP10 heterodimers can also trigger mitosis, a process of cell division that requires cell rounding to be initiated ( 130 ). The full differences between these functional heterodimers are still unclear, as contributions of other ZIP transporters, such as ZIP5, have yet to be clarified.…”
Section: Functional Diversification By Multilayers Of Protein Interacmentioning
confidence: 99%
“…The essential role of extracellular zinc in cell proliferation was suggested by the ability of zinc to reverse a zinc chelation-induced suppression of cell cycle progression ( 187 ). When the cell was ready to progress into mitosis, ZIP6–ZIP10 heterodimer was upregulated on the plasma membrane to increase zinc influx to specifically activate the normal processes of mitosis such as microtubule reorganization and chromosome condensation ( 130 ). This mechanism was demonstrated in part by the correlation between antibody inhibition of ZIP6 or ZIP10 and the pause of mitotic initiation, even in the presence of mitotic inducers such as nocodazole ( 130 ).…”
Section: Cellular Zinc Signalingmentioning
confidence: 99%
“…ZIP5 was overexpressed during esophageal tumorigenesis, and played a vital role in esophageal cancer progression [ 25 ]. ZIP10 was involved in the development of breast cancer by forming a heteromer with ZIP6 [ 26 , 27 ]. ZIP14 was identified as a critical mediator of cachexia development in several metastatic cancers, such as metastatic pancreatic, colon, and breast cancers [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%